Vicious and virtuous circle: The political economy of unemployment in interwar UK and USA - Ken Matthews; Patrick Minford; Ruthira Naraidoo (Cardiff University, Cardiff Business School, 2006)
This paper develops a political economy model of multiple unemployment equilibria to provide a theory of an endogenous natural rate of unemployment. This model is applied to the UK and the US interwar period which is remembered as the decade of mass unemployment. The theory here sees the natural rate and the associated path of unemployment as a reaction to shocks (mainly demand in nature) and the institutional structure of the economy. The channel through which these two forces feed on each other is a political economy process whereby voters with limited information on the natural rate react to shocks by demanding more or less social protection. The reduced form results obtained con?rm a pattern of unemployment behaviour in which unemployment moves between high and low equilibria in response to shocks.
Keywords: E24; E27; P16; 330; Equilibrium unemployment; political economy; “vicious” and “virtuous” circles; bootstrapping; forecasting